Quality of care and satisfaction of users treated via gynecologic oncology telemedicine at Hospital Nacional Edgardo Rebagliati Martins of EsSalud from August to October 2021 - Aguilar-Ramos, Pedro (2022)
Objective: To determine the relationship between quality of care and satisfaction of users treated via gynecologic oncology telemedicine from August to October 2021. Materials and methods: An observational, cross-sectional and prospective study conducted with 302 users. Instruments: modified SERVPERF questionnaire to evaluate the quality of care, MINSA’s checklist to evaluate the structure, and telemedicine time record sheet to evaluate the process. Data was analyzed using IBM SPSS Statistics V27 and Fisher's F test with p < 0.05. Results: Compliance with the structure was 66.67 % according to MINSA. Regarding the process, patient waiting time to get a telemedicine appointment was 1 to 7 days in 53.31 %, patient waiting time to begin a telemedicine consultation was < 10 minutes in 64.22 %, and telemedicine length was 11 to 15 minutes in 41.39 %. Quality of care dimensions such as reliability, responsiveness, safety, empathy and tangible aspects were good in 91.72 %, 90.06 %, 91.05 %, 88.41 % and 92.39 %, respectively. Quality of care was good, fair and bad in 95.37 %, 4.32 % and 0.31 %, respectively. Satisfaction was high, medium and low in 88.35 %, 7.93 % and 3.72 %, respectively. According to Fisher's F test, the relationship between quality of care, with its respective dimensions, and satisfaction was < 0.000. Conclusions: There is a relationship between quality of care and satisfaction of users of telemedicine. The process meets the established requirements and the structure is still in process. Quality of care is good and satisfaction is high.